Internalisasi Nilai-Nilai Islam Moderat Melalui Program Dakwah Imamah Khitobah Wa di Pondok Pesantren Al-Iman Ponorogo - Dafiyatur Rurojifah; Khafidoh (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
Islamic boarding schools have an important role in forming the moderate character of students. The rise of intolerance, radicalism and extremism that occurs in Indonesia is a particular concern for the learning system in Islamic boarding schools. Moreover, the perspective of some groups has emerged that the learning system in Islamic boarding schools produces students who have conservative and even radical thinking. The concept of Islam that rahmatan lil 'alamin as a basis for moderate Islamic values needs to be instilled in the souls of every student in Islamic boarding schools in order to form a moderate character. Al-Iman Islamic boarding school as an educational institution that is committed to producing a moderate generation has the Imamah Khitobah wa Dakwah program organized by the Kulliyatul Mu'allimin/at Division (KMI) as a form of providing students with training and instilling the values of moderation. This research aims to explore moderate Islamic values and analyze the process of internalizing moderate Islamic values at the Al-Iman Ponorogo Islamic boarding school for class VI KMI students (Kulliyatul Mua'alimin/Mu'allimat al-Islamiyah) through the Imamah Khitobah wa Dakwah Program. This program was held to protect students from radical thoughts and extremism, so that students can implement moderate Islamic values in social life. This research uses a qualitative approach with a case study type of research. The sources of data obtained were asatidz and ustadzat of the Al-Iman Islamic boarding school, students and alumni. Data collection techniques use observation, interviews and documentation techniques. The results of the research show that the internalization of moderate Islamic values through the Imamah Khitobah wa Dakwah program held at the Al-Iman Islamic boarding school produces a moderate learning concept and habituation patterns for students to behave moderately. Through the concept of moderate learning, students can understand the characteristics of moderation based on the Islamic values of rahmatan lil 'alamin. Meanwhile, through habituation patterns, students practice taking a moderate attitude and respecting different opinions in dealing with every problem, especially in religious matters. To contribute to previous studies, this study also attempts to map and analyze the role of Islamic boarding school stakeholders in the massive and structured internalization of moderate Islamic values.